Pengaruh Faktor Kualitas Jasa Perguruan Tinggi Jarak Jauh (PTJJ) terhadap Kepuasan Mahasiswa dan Niat Menyelesaikan Kuliah (Studi Kasus Mahasiswa Fakultas Ekonomi Universitas Terbuka) - Maria, Maya; Hadiwidjaja, Rini Dwiyani; Mulyana, Andy (IPB University, 2015)
This study aims to determine the effects of open distance learning service quality dimensions consisting of the way of learning, tutoring and teaching, modules, student services, programs of study, tuition and fees, physical facilities to student satisfaction and the behavioral intentions of completing the study at Universitas Terbuka (UT). Thisresearch analysis unitswere the students of the Faculty of Economic, Universitas Terbuka (FEKON-UT) who registeredin 2012with a population of 2085 people. The method of sample selection was convenience samplingmethod to the college students who have taken at least one semester. The data were analyzed from 161 respondents spread in 7 UPBJJ-UTthroughout Indonesia with a certain proportion. To obtain the data, this study used survey methods of primary data and secondary data. Analysis tool to test the hypothesis is a structural equation modelling (SEM) with Partial Least Square (PLS). The finding of this studywere the significance effects on :1) the quality of services to satisfaction of students; 2) the quality of services to the intention of completing studying at UT; and 3) student satisfaction to the intention of completing college at UT.Keywords: service quality, student satisfaction, open distance learning, intention to finish college